Photonic crystal fiber based terahertz sensor for cholesterol detection in human blood and liquid foodstuffs - Md. Moshiur Rahman (Sensing and Bio-Sensing Research, 2020)
Low density lipoprotein (LDL) cholesterol is the leading cause of heart diseases, peripheral artery diseases, and stroke. An accurate, flexible, and efficient detection process is very urgent for identifying the cholesterol. In this context, an octagonal shaped hollow core with eight head star cladding structured photonic crystal fiber (PCF) has been proposed in this paper for cholesterol sensing in liquid analytes (human blood, cocking oil, liquid foods, etc.). The sensing performances of proposed PCF are evaluated through the COMSOL multiphysics software where the finite element method (FEM) has been used as a solver. The numerical investigation of the presented PCF structure exhibits highly sensitive characteristics for cholesterol detection in liquid samples and the proportion is 98.75% at 2.2 THz frequency. It also reveals negligible confinement loss of 3.14 × 10−20 cm−1 and low effective material loss of 0.0008 cm−1 at the same operating point. Furthermore, the commercial development feasibility of designed PCF in the existing manufacturing environment and other crucial optical properties such as effective area, dispersion, numerical aperture are also discussed in detail.